Isolation, Production and Characterization of Thermostable Lipase from Bacillus Sp. Strain L2 - Mohammed Mukred, Abdul Daim (2004)
A thermostable lipolytic endospore forming Bacillus sp. strain L2 was isolated from a hot spring (91oC) in Slim River, Perak, Malaysia. Nutritional studies showed that casamino acid was the best nitrogen source while trehalose and Tween 60 were the best carbon source and substrate respectively, for lipase production. The enzyme production was promoted in the presence of metal ions such as Ca2+, Cu2+, Fe2+, Co2+, Zn2+, and Sr2+. The optimum lipase production was obtained in the presence of CaCl2. Physiological study indicate that, this strain showed optimal lipase production after 28 h of incubation at 70 oC with 1% starting inoculum. The enzyme was purified to homogeneity by ammonium sulphate precipitation and affinity column chromatography (Heparin), with 3 fold increase in specific activity and 48.9 % recovery. The purified enzyme produced a single band on SDS-PAGE. Its molecular mass was estimated to be 43 KDa. The optimum pH and temperature for L2 lipase were determined to be 7.0 and 80 oC, respectively. The III lipase was very stable for 2 h at 80 oC. The stability at higher temperature was shown to be calcium dependent. The lipase activity was enhanced by Fe2+and Ca2+ while Cu2+ inhibited it. The enzyme activity was strongly inhibited by PMSF and completely inhibited by pCMB. Substrates such as olive oil and sesame oil enhanced the lipase activity.